Inclusive Policy? An Intersectional Analysis of Policy Influencing Women’s Reproductive Decision‐Making - Haintz, Greer Lamaro (2023)
Policy can be used and experienced as a tool for social inclusion or exclusion; it can empower or disenfranchise. Women’s reproductive decision‐making and health is impacted by policy, and women’s experiences of diverse and intersecting marginalised social locations can influence their experiences of policy. This research aimed to explore how intersectionality is considered within Victorian state government policies that influence and impact women’s reproductive decision-making. A systematic search of Victorian (Australia) government policy instruments was undertaken, identifying twenty policy instruments. Policies were analysed using an intersectional policy analysis framework using a two‐stage process involving deductive coding into the domains of the framework, followed by inductive thematic analysis within and across domains. Findings reveal inconsistencies within and across policies in how they consider intersecting social relations of power in the representation of problems, women’s positionings, policy impacts, and policy solutions. These gaps could exclude and marginalise individuals and groups and contribute to systemic inequities in women’s reproductive decision-making and the outcomes of those decisions, particularly among already marginalised groups. The lack of women’s voices in policy further excludes and marginalises those impacted by the policy and limits the representation of all women in policy. Policy development needs to meaningfully involve women with diverse and intersecting marginalised social locations, and critical reflexivity of all stakeholders, to ensure policies can better account for the experiences of, and impacts upon, women who are marginalised and effect change to promote social inclusion and equity in women’s reproductive decision‐making.